2023
DOI: 10.21203/rs.3.rs-2144223/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and Organizing of Home-Based Care for Older Adults in Different Countries: Scoping Review

Abstract: Background Demographic changes, growing long-term living costs, personal preferences, and policies encouraging aging in place have increased the importance of home-based long term care (LTC). It seems that sharing the experiences of leading countries will help to provide effective system. As a result, this review aims to explain the structure of home-based LTC for older adults in different countries. Methods A scoping review was performed for literature on home-based care for older adults published in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Similar to the results of this study, universal coverage of long-term care insurance can solve the needs of older adults with chronic conditions in the community [75]. According to various pieces of literature, quality care should cover dimensions such as a competent workforce, patient satisfaction, person-centered care, patient involvement in decision-making, and compliance with care standards [76,77]. In leading countries in HC, such as Germany and Japan, issues such as long-term care insurance, benefts, rights, and ethics in care are among the passed laws [78,79].…”
Section: Discussionsupporting
confidence: 68%
“…Similar to the results of this study, universal coverage of long-term care insurance can solve the needs of older adults with chronic conditions in the community [75]. According to various pieces of literature, quality care should cover dimensions such as a competent workforce, patient satisfaction, person-centered care, patient involvement in decision-making, and compliance with care standards [76,77]. In leading countries in HC, such as Germany and Japan, issues such as long-term care insurance, benefts, rights, and ethics in care are among the passed laws [78,79].…”
Section: Discussionsupporting
confidence: 68%
“…As age increases, it is expected that the former decreases and the latter increases, which confirms our results. Furthermore, other studies have confirmed that the occurrence of against-the-rule astigmatism increases with age, possibly due to the relaxation of eyelid muscles and reduced eyelid pressure (40)(41)(42).…”
Section: Discussionmentioning
confidence: 84%